A multiplicidade dos padrões de sustentabilidade relativos a gases de efeito estufa - Beneducci, Giovanna Becalete (Universidade Federal de São Carlos, 2022)
According to the most recent report published by the Intergovernmental Panel on Climate Change, the increasing attention to climate change is mainly due to the steady rise in the global temperature over the past few decades. Currently, the world’s temperature is about 1°C above pre-industrial levels. As the challenge of climate change increases, shareholders and consumers are demanding new actions from companies in this fight. In this way, sustainability standards related to greenhouse gases appear to certify and provide an additional guarantee in the validity of the reduction of emissions by an organization, or to increase a company’s reputation that wishes to adhere to a standard, adding value to the product and proving its suitability within the consumer requirements. However, there is currently a proliferation of these sustainability standards in almost all sectors and countries, which can imply in a lack of harmonization between the criteria of these standards and, subsequently, contribute to the increase of compliance costs in adhering to a certain standard. Therefore, it is highly relevant to understand the relationship between standard multiplicity and trade costs. This study seeks to understand the objective of each sustainability standard related to greenhouse gases and, also, to verify if there are overlapping criteria between them. The results showed low overlap between the criteria of the analyzed standards. Furthermore, it was also evident that pairs composed of a carbon footprint standard and an emissions reduction standard can benefit organizations that wish to be certified by both together, as they had higher overlap rates.
The multiplicity of sustainability standards related to greenhouse gases
Keywords: Padrões de sustentabilidade; Gases de efeito estufa; Sobreposição; Sustainability standards; Greenhouse gas emissions; Overlap; CIENCIAS SOCIAIS APLICADAS::ECONOMIA